Preparation sodium salts of phenylalanine, glycine and alanine complexes by using K2PtCl6, Cu(NO3)2.3H2O, HgCl2 and ZnCl2 - Aisha B. A. Elmagtof; Omar A. S. Miftah; Afaf M. A. Elmagtof (African Journal of Advanced Pure and Applied Sciences, 2024)
applications of complexes are very important in different sectors like the pharmaceutical industrial. So, this study aimed to preparation sodium salts of amino acids complexes by using K2PtCl6, Cu (NO3)2.3H2O, HgCl2 and ZnCl2 as a ligand reaction with the sodium salts of the following amino acids: glycine (glyH), L-alanine (alaH), L-phenylalanine (pheH). The following complexes were isolated: Na [Pt(gly)Cl4] .0.5C2H5OH, [Cu(ala)2].0.5C2H5OH, [Pt(ala)3Cl].C2H5OH.4H2O, [Pt(phe)2Cl2].0.5C2H5OH.1.5H2O, [Hg(phe)2].9H2O, [Zn(phe)2].C2H5OH. The isolated complexes have been characterized by their elemental analysis’s solubility, conductivity measurements, IR, electronic absorption and C13 NMR spectra.